Physical Activity and Cancer Status Among Middle-Aged and Older Chinese: A Population-Based, Cross-Sectional Study - Zhu, Chunsu; Lian, Zhiwei; Chen, Ying; Wang, Jianmin (Frontiers in Physiology, 2022)
Background: The relative contribution of demographic and lifestyle behaviors to the association between physical activity (PA) and cancer is poorly understood. This study assesses the relationship between PA level and cancer status considering the full activity spectrum within a large and representative Chinese population. Methods: Data were derived from the Chinese Health and Retirement Longitudinal Study (using four-stage stratified probability-proportional-to-size sampling), including 416 cancer survivors and 14,574 individuals without cancer from 28 provinces in China. Cancer status and sites were self-reported, and PA, other health behaviors (e.g., smoking, drinking) and comorbidities (e.g., hypertension, diabetes) were assessed by questionnaire. The total PA score was calculated using metabolic equivalent (MET) multipliers. Multivariable logistic regression was used to estimate differences in PA levels between cancer survivors and those without a cancer diagnosis, adjusted for potential confounding factors. Results: Cancer survivors (416, 2.8%) were more likely to be women than men (65.4% vs. 34.6%). They were older (age ≥ 65 years, 43.8% vs. 38.9%) and more likely to be overweight (18.3% vs. 13.3%), to be depressed (49.5% vs. 37.6%), to have quit smoking (17.8% vs. 14.4%), to drink less (17.5% vs. 26.6%), to sleep less (65.9% vs. 56.8%) and to have more chronic comorbidities (≥ 2 comorbidities, 26.0% vs. 19.2%) than those without cancer. There were significant associations between cancer status and participating in vigorous-intensity activity for at least ten minutes every week compared to the inactive group (OR= 0.56, 95% CI=0.39-0.80), while no differences were observed between the moderate and light activity groups. Individuals spending more than half an hour performing moderate or vigorous intensity activity every day were significantly less likely to report a cancer diagnosis than inactive individuals (moderate OR=0.64, 95% CI=0.48-0.86; vigorous OR=0.50, 95% CI=0.37-0.68). Participants spending more than two hours performing light, moderate or vigorous intensity activity reported fewer cancer cases than their inactive counterparts. In addition, there was a positive dose-response relationship between the total PA score and cancer status (P-trend < 0.001). Conclusion: Associations between PA and cancer status were independent of demographics, lifestyle confounders and comorbidities. Performing adequate PA may lower the risk of cancer.